Professional Learning Community sebagai Upaya Mengembangkan Profesionalisme Guru PAI di Madrasah - Fadlilah, Nur; Jannah, Nurul (JOIES (Journal of Islamic Education Studies), 2017)
This article uses content analysis to analyze the problems in it. This paper aims to: 1) Explain the definition and function of the Professional Learning Community (PLC). 2) Explain the PLC model. 3) explain the dimensions of the PLC in developing teacher professionalism. The results of the analysis of this paper conclude that to develop teacher professionalism, Professional Learning Community (PLC) is considered to be the most appropriate alternative solution. There are several reasons underlying this conclusion, including; 1) PLC implementation does not require large costs, and 2) In some models, especially those based on electronics, PLCs are very efficient in terms of power, place and time. Through this PLC it is hoped that it can improve the technical abilities of teachers in managing material that is their responsibility, skilled and wise in adapting any dynamics of community change or educational policy changes so that they truly become professional teachers.